Natural Killer Cells: Friend or Foe in Metabolic Diseases? - Li, Yi; Wang, Fangjie; Imani, Saber; Tao, Ling; Deng, Youcai; Cai, Yue (Frontiers in Immunology, 2021)
Abstract The worldwide epidemic of metabolic diseases, especially obesity and other diseases caused by it, has shown a dramatic increase in incidence. A great deal of attention has been focused on the underlying mechanisms of these pathological processes and potential strategies to solve these problems. Chronic inflammation initiated by abdominal adipose tissues and immune cell activation in obesity is the major cause of the consequent development of complications. In addition to adipocytes, macrophages and monocytes, natural killer (NK) cells have been verified to be vital components involved in shaping the inflammatory microenvironment, thereby leading to various obesity-related metabolic diseases. Here, we provide an overview of the roles of NK cells and the interactions of these cells with other immune and nonimmune cells in the pathological processes of metabolic diseases. Finally, we also discuss potential therapeutic strategies targeting NK cells to treat metabolic diseases.